+0  
 
0
687
1
avatar

\(2x-3 = {x-2y \ \over 4}\frac{}{}\)

\(6x-4(x-2y)=x+6y\)

 

Was ergibt das ?

Schöne grüße

 20.02.2016
 #1
avatar+14537 
0

Guten Abend !

 

Lösen des Gleichungssystems  mit dem Additionsverfahren (Subtraktionsverfahren) :

 

(1)   Gleichung mit  4  multiplizieren     =>   8x-12=x-2y  =>  \(7x+2y=12\)

 

(2)   ausmultiplizieren    =>    6x-4x+8y=x+6y         =>                \(x+2y=0\)

 

(1) - (2)    =>       \(6x=12\)         =>    \(x=2\)

 

X=2  in  (2) einsetzen       =>   \(2+2y=0\)         =>    \(y=-1\)

 

Lösung :    x = 2       y = -1

 

 Probe:  Rechner     2*2-3 = 1        (2-2*(-1))/4 = 1

                                   6*2-4*(2-2*(-1) = -4           2+6*(-1) = -4

 

Gruß Radix smiley !

 20.02.2016

27 Benutzer online

avatar
avatar
avatar
avatar